2020
DOI: 10.1088/1757-899x/775/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

‘Smart city’ system as an asset of cultural landscapes development

Abstract: The article touches upon the idea of ‘smart city’ and ways of how it could be applied to advancing contemporary urban environment. Highlighting variety of definitions this popular term demonstrates there is posed a problem of apprehension both in theory and architectural practice. Authors place particular importance on social aspects of the method to be improved to make it adaptable to integrate with cultural heritage. Having referred to successful examples of heritage technological improvement authors claim ‘… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Various studies have shown that cultural landscapes and urban planning are closely related to the evolution of technology and communications, and thus it takes advantage of new technologies to achieve better solutions on the management side. [1] [2] [3] In this respect, my research for the past two years has been focused on the Smart side of Cultural Landscapes. How to tackle with this concept and what it implies when it comes to the planning process at the local and regional level.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that cultural landscapes and urban planning are closely related to the evolution of technology and communications, and thus it takes advantage of new technologies to achieve better solutions on the management side. [1] [2] [3] In this respect, my research for the past two years has been focused on the Smart side of Cultural Landscapes. How to tackle with this concept and what it implies when it comes to the planning process at the local and regional level.…”
Section: Introductionmentioning
confidence: 99%